2018
DOI: 10.1111/mmi.14148
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles and diverse regulation of the Ras/cAMP/protein kinase A pathway in Candida albicans

Abstract: Summary Candida albicans is a major fungal pathogen of humans, causing both superficial and life‐threatening systemic infections in immunocompromised people. The conserved Ras/cAMP/PKA pathway plays a key role in regulating multiple traits important for the virulence of C. albicans such as cell growth, yeast‐hyphal transition, white‐opaque switching, sexual reproduction and biofilm development. Diverse external signals influence cell physiology by activating this signaling pathway. The key components of the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 98 publications
3
84
0
1
Order By: Relevance
“…Huk et al suggested that deletion of RAP1B reduces the size and incidence of TC mediated by protein kinase A (PKA) in an in vivo model . Other advanced investigations implied that RAP1B is a downstream target of the PKA signal pathway, which is associated with tumorigenesis of TC . Another study reported that RAP1B plays an oncogenic role in esophageal squamous cell carcinoma by activating the Wnt/beta‐catenin cascade .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huk et al suggested that deletion of RAP1B reduces the size and incidence of TC mediated by protein kinase A (PKA) in an in vivo model . Other advanced investigations implied that RAP1B is a downstream target of the PKA signal pathway, which is associated with tumorigenesis of TC . Another study reported that RAP1B plays an oncogenic role in esophageal squamous cell carcinoma by activating the Wnt/beta‐catenin cascade .…”
Section: Discussionmentioning
confidence: 99%
“…24 Other advanced investigations implied that RAP1B is a downstream target of the PKA signal pathway, which is associated with tumorigenesis of TC. 25 Another study reported that RAP1B plays an oncogenic role in esophageal squamous cell carcinoma by activating the Wnt/beta-catenin cascade. 26 RAP1B is a promising therapeutic target for the TC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While both SNF5 / snf5 and CYR1 / cyr1 mutants had no perceptible fitness defect, the SNF5 / snf5 CYR1 / cyr1 strain exhibited a growth defect similar to that of snf5 / snf5, suggesting that Snf5 and the adenylyl cyclase Cyr1 operate on the same pathway ( Figure 7D ). Intriguingly, even if Cyr1 is a key component and an effector of Ras1 pathway [49], SNF5 did not interact genetically with RAS1 . Previous study had shown that C. albicans filamentation in response to carbon dioxide depends on Cyr1, but not on Ras1, suggesting that Cyr1 controls specific functions that are independent from the Ras pathway [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with this, mutants of SWI/SNF subunits that exhibited metabolic flexibility defect in our study such as snf6 and snf5 or swi1 and arp9 belong to the same functional sub-complexes in the budding yeast. Alternatively, differential requirement of SWI/SNF subunit in C. albicans could be explained by the fact that deleting certain subunits might led to a non-functional aberrant complex that remains attached to its target promoters [58] and prevents redundant chromatin remodelling complex such as RSC to bind DNA and consequently compensates loss of SWI/SNF chromatin remodelling activity [49,50,51]. Accordingly, in S. cerevisiae , loss of Snf5 did not affect Snf2 occupancy to gene promoters and resulted in an aberrant SWI/SNF complex that functions as a dominant negative mutation by blocking recruitment of other redundant compensating chromatin remodelers [60].…”
Section: Discussionmentioning
confidence: 99%
“…In most of the pathogenic fungi, Ras pathway signaling is determined as critical virulence factor [33]. e Ras pathway signaling is involved in pathogenesis, morphological transitions, nutrient sensing and acquisition, sexual reproduction, and stress responses of fungi [34]. e results also evidenced that the pathogenicity and virulence of P. expansum was weakened, and its growth was eventually inhibited by M. guilliermondii.…”
Section: Castellote Et Al Investigated the Molecular Expression Ofmentioning
confidence: 99%